Trilemmas: Gorgias’ PTMO Between Zeno and Melissus - Rossetti, Livio (Peitho. Examina Antiqua, 2017)
The present paper makes the following points. (1) The summary given in Sextus Emp. Math. VII is of much greater value than usually acknowledged, since it preserves several key elements of Gorgias’ communicational strategy. (2) A sketchy trilemma is available in the opening sentence of Philolaos (DK 44B2) as well as in a passage of Plato’s Parmenides. This is evidence in favor of the hypothesis that the very first known trilemma was devised by Gorgias and not by Sextus himself or Aenesidemus. (3) Not unlike Zeno, Gorgias enjoyed to be neither serious nor joking, but remained somewhat halfway. This point is seldom acknowledged, though it is crucial in order to understand that he pretends to claim (e.g. that p), but his claims do not amount to any points of doctrine. (4) That he remains halfway should not prevent us from appreciating some of his ideas, but, at the same time, we should not expect full intellectual adhesion to what he tells us. Besides, something similar occurs in most of Plato’s dialogues. (5). Gorgias owes a lot to Melissus.